2015
DOI: 10.1590/s0102-865020150050000007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenesis and epithelial coating of skin wounds in rats treated with angico extract (Anadenanthera colubrina var. cebil)

Abstract: PURPOSE:To evaluate the effects of angico bark extract (Anadenanthera colubrina var. cebil) in the healing process of the skin of rats. METHODS:Twenty adult male rats were divided into four groups of five animals each, according to the respective postoperative days, as follow: G4, G7, G14 and G21. Each group received two incisions on skin and subcutaneous tissue in the right and left antimere of the thoracic region, separated by a distance of 2 cm. The right lesion was treated daily with saline and the left wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…The authors demonstrated the similarity of the two methods. Pessoa et al (2015) also used GT and PR staining to evaluate new collagen in rat skin samples. The authors reported good efficacy of the method to achieve realistic and satisfactory data.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated the similarity of the two methods. Pessoa et al (2015) also used GT and PR staining to evaluate new collagen in rat skin samples. The authors reported good efficacy of the method to achieve realistic and satisfactory data.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are closely correlated with the increased activation of NF- κ B and ERK signaling pathways. Furthermore, the enhanced activities of NF- κ B and ERK pathways may represent major molecular targets of PAE, which accelerate wound healing by upregulating the expression of a series of genes involved in cell proliferation, fibrogenesis, reepithelialization, and remodeling [2, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…During the final stage of wound healing, granulation tissue changes into mature scar tissue as a result of resorption of exudate and strong collagen synthesis. The healing process depends on the individual characteristics of an organism, regenerative capacity and the scale of damage and can last from several weeks to several months [ 292 , 293 , 294 ].…”
Section: The Effect Of Phenolic Compounds On Healing Of Incised Anmentioning
confidence: 99%